Hubungan Dukungan Sosial Teman Sebaya Dengan Stres Akademik Dalam Penyusunan Skripsi Pada Mahasiswa Akhir - Zahrah, Lina Az; Fitriana, Siti; Ismah, Ismah (Universitas PGRI Semarang, 2026)
This study aimed to look into the link between social support from peers and academic stress levels among students wrapping up their dissertations. It used a quantitative, correlational design and involved 113 participants, who filled out questionnaires via Google Forms. The measurement tools were both valid and reliable, with Cronbach’s Alpha scores of 0.926 for peer social support and 0.938 for academic stress. Data were analysed using Pearson’s correlation. The results showed that peer social support was generally high, with the largest share of respondents at 45.1%, while most students reported low levels of academic stress, at 44.2%. The correlation test gave a Pearson correlation of 0.266 with a significance of 0.004, indicating a positive, statistically significant relationship, although the strength of the link was fairly low. Peer social support accounted for 7.1% of the variation in academic stress, leaving 92.9% influenced by other factors outside this model. In short, while social support from friends does play a role, it’s a limited one when it comes to affecting students’ academic stress during dissertation writing.